2020
DOI: 10.9734/ajfar/2020/v6i130086
|View full text |Cite
|
Sign up to set email alerts
|

Water Quality Assessment of Shitalakhya River

Abstract: Water quality is the key of environmental concern because of its important provision of water for drinking and domestic purpose, irrigation and aquatic life including fish and fisheries. The present study was conducted to assess the surface water quality of the Shitalakhya River from January, 2017 to December, 2018. Temperature, pH, EC, TDS, TSS, BOD5, Alkalinity, Total Hardness, Calcium Hardness, Magnesium Hardness, Chloride, Dissolved Silica, Total Iron concentration and Turbidity in water samples have been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…They indicate that water at the surveyed sites was fresh, slightly saline, slightly alkaline and moderately saturated with oxygen. Water pH, EC, TDS, salinity and DO were within standard limits, while water temperature, ORP and resistivity showed deviations from good conditions (Wetzel 1983;Horne & Goldman 1994;Al-Badaii et al 2013;Adhena et al 2020;Alam et al 2020). The sampling season, agricultural and nutrient runoff, domestic and industrial effluents were the major causes of fluctuations in water quality parameters, similar to previous studies conducted in habitats of the Upper Indus River (Ali et al 2007;Barinova et al 2013Barinova et al , 2016.…”
Section: Nitellopsis Obtusa (Desvaux) Jgroves 1919mentioning
confidence: 99%
“…They indicate that water at the surveyed sites was fresh, slightly saline, slightly alkaline and moderately saturated with oxygen. Water pH, EC, TDS, salinity and DO were within standard limits, while water temperature, ORP and resistivity showed deviations from good conditions (Wetzel 1983;Horne & Goldman 1994;Al-Badaii et al 2013;Adhena et al 2020;Alam et al 2020). The sampling season, agricultural and nutrient runoff, domestic and industrial effluents were the major causes of fluctuations in water quality parameters, similar to previous studies conducted in habitats of the Upper Indus River (Ali et al 2007;Barinova et al 2013Barinova et al , 2016.…”
Section: Nitellopsis Obtusa (Desvaux) Jgroves 1919mentioning
confidence: 99%
“…industries situated on the riverbank area affects tremendously the quality of Sitalakhya River water (Tables 1 and 2 ). Besides, the pollutant loads were also coming from Balu River and Dhaleshwari River [ 37 , 105 , 106 , 107 ]. The drinking water treatment plant in Saidabad receives raw water from Sitalakhya River close to Demra ghat.…”
Section: River Pollution In Bangladeshmentioning
confidence: 99%
“…Saha et al (2012) showed a pH of 7.31 in Azimpur colony pond water. Alam et al (2020) reported a similar pH (6.50-7.60) in Shitalakshya River water. According to standard (De 1999), the electrical conductivity (EC) value of surface water is <350 μs/cm.…”
Section: Resultsmentioning
confidence: 67%